ANALISA KINERJA RUAS JALAN KEBON AGUNG KOTA SAMARINDA - SUSANTO, HERI (KURVA S JURNAL MAHASISWA, 2018)
Kebon Agung road segment in Samarinda city is included with a moderate level of activity, because along the road there are shops, factories, workshops and schools. The road segment is one of the connecting roads between cities, thus this road is very useful in serving large enough traffic. As a road that has an important role in traffic in Samarinda City, conditions on the Kebon Agung road especially at some points, traffic such as increased delay. Performance analysis of urban road segments using the Indonesian Road Capacity Manual (MKJI) 1997, with performance indicators namely traffic flow (Q), capacity (C), degree of saturation (DS), free flow velocity implemented with various work indicators namely free flow speed , and analyze the level of service on the road. Based on the results of research and analysis of the results of field data collection at the Kebon Agung Kota Samarinda road location on Monday had a traffic flow value (Q) = 1061.1 pcu / hour, capacity value (C) = 2672,5704 pcu / hour, degree saturation (DS) = 0.40, with a light travel speed of 33.9 km / hour and a travel time of 1.8 minutes. On Wednesday the value of traffic flow (Q) = 1097.15 pcu / hour, capacity value (C) = 2672,5704 pcu / hour, degree of saturation (DS) = 0,41, with travel speed of light vehicles 33,9 km / hour and travel time of 1.8 minutes. On Saturday has a traffic flow (Q) = 1111.7 pcu / hour, capacity value (C) = 2672,5704 pcu / hour, degree of saturation (DS) = 0,42, with light travel speed of 33,9 vehicles km / hour and travel time of 1.8 minutes. On Sunday has a traffic flow value (Q) = 1143.35 pcu / hour, capacity value (C) = 2672,5704 pcu / hour, degree of saturation (DS) = 0,43, with travel speed of light vehicles 33,9 km / h and travel time 1.8 and service level (Level Of Service / LOS) on Monday, Wednesday, Saturday and Sunday are categorized B. The performance of Kebon Agung Street is still in a stable current condition and has not been categorized as a traffic jam, because of the value DS is still below 1.00. The high class of side barriers in the current conditions it is necessary to do further studies to be able to improve the performance of the Kebon Agung road in Samarinda city